Losing control in pre-adoption services: Finnish prospective adoptive parents emotional experiences of vulnerability - Pia K Eriksson (Social Work and Society, 2016)
This article argues that the institutional context of pre-adoption services in inter-country adoptions fosters straining emotions in prospective adoptive parents through controlling practices, thus putting clients in a vulnerable situation. The article analyses the power and emotions involved in the relationship between the client and the professional, based on nineteen narrative interviews conducted with former prospective adoptive parents in Finland. The results of the study suggest that prospective adoptive parents perceive power through three types of controlling practices: support for emotional readiness, entitlement to professional interpretations, and time and information control. In combination with the broader social setting of the inter-country adoption process, these practices give rise to a dependency that fosters emotions of anger and fear at differing levels of intensity. The implications of the study call for an acknowledgement of power and emotion as important issues in pre-adoptions services, and prompt changes to be undertaken in professional practice and discourse, through collaborative definitions of aims and needs within the services.